Geomorphological and seismostratigraphic evidence for multidirectional polyphase glaciation of the northern Celtic Sea. (21st February 2020) - Tóth, Zsuzsanna; McCarron, Stephen; Wheeler, Andrew J.; Wenau, Stefan; Davis, Stephen; Lim, Aaron; Spiess, Volkhard
ABSTRACT: High‐resolution seismic and bathymetric data offshore southeast Ireland and LIDaR data in County Waterford are presented that partially overlap previous studies. The observed Quaternary stratigraphic succession offshore southeast Ireland (between Dungarvan and Kilmore Quay) records a sequence of depositional and erosional events that supports regional glacial models derived from nearby coastal sediment stratigraphies and landforms. A regionally widespread, acoustically massive facies interpreted as the 'Irish Sea Till' infills an uneven, channelized bedrock surface overlying irregular mounds and deposits in bedrock lows that are probably earlier Pleistocene diamicts. The till is truncated and overlain by a thin, stratified facies, suggesting the development of a regional palaeolake following ice recession of the Irish Sea Ice Stream. A north–south oriented seabed ridge to the north is interpreted as an esker, representing southward flowing subglacial drainage associated with a restricted ice sheet advance of the Irish Ice Sheet onto the Celtic Sea shelf. Onshore topographic data reveal streamlined bedforms that corroborate a southerly advance of ice onto the shelf across County Waterford. The combined evidence supports previous palaeoglaciological models. Significantly, for the first time, this study defines a southern limit for a Late Midlandian Irish Ice Sheet advance onto the Celtic Sea shelf. © 2020 John Wiley & Sons, Ltd.